Amblyomma scutatum Neumann, 1899 (Ixodida: Ixodidae) parasitizing Ctenosaura similis (Gray, 1831) (Squamata: Iguanidae) in Costa Rica - Bermúdez Castillero, Sergio (2023)
A total of 38 ticks were collected on black spiny-tailed iguana, Ctenosaura similis, in a secondary dry forest from northern lowlands of Guanacaste, Costa Rica. At the time of finding, the animal has not mobility of the hind legs and tail. Ticks were identified morphological and molecularly as Amblyomma scutatum. PCR amplification tests to Rickettsia, Anaplasmataceae and Borrelia were negative. Possible caused of the lack of mobility is discussed.